Superoxide anion monitoring in epileptic brains with a near-infrared fluorescent probe - Ying, Weiwu; Dong, Fuxing; Shi, Yifan; Zhan, Ziyi; Wang, Shuwan; Lv, Li; Liu, Huizhen; Liu, Ling; Zheng, Youguang; Zhang, Ling (Dyes and pigments, 2023)
Epilepsy is a chronic neurological disorder, and the pathophysiological progression to status epilepticus is closely associated with oxidative stress. Superoxide anions (O2•-), as the main, most important precursor of other reactive oxygen species (ROS), play a crucial role in seizure-induced brain damage. However, detecting the actual O2•- levels and understanding the physiological roles of O2• in epileptic brains remain challenging due to the lack of effective in vivo detection tools. Herein, a new near-infrared fluorescent probe, MB-SO, was prepared for the determination of endogenous O2•- in brains experiencing pentylenetetrazole (PTZ)-induced epileptic seizures. MB-SO exhibits high sensitivity (detection limit of 14 nM), good selectivity and a fast response towards O2•-. MB-SO was applied in situ to monitor endogenous O2•- in living HT-22 cells and living mice. Using this probe, we visualized and quantitatively detected endogenous O2•- for the first time in the hippocampi of PTZ-induced epileptic mouse brains. MB-SO also displayed a positive correlation between high O2•- levels in epileptic brains and epileptogenesis. These results indicated that the probe MB-SO is an efficient tool for monitoring endogenous O2•- in vivo and exploring the pathogenesis of epilepsy. •A novel near-infrared fluorescent probe for highly sensitive detection of O2•- was reported.•This probe exhibits high sensitivity (detection limit of 14 nM) and a fast response towards O2•-.•MB-SO was utilized to detect endogenous O2•- in the hippocampus of PTZ-induced epileptic mouse brains.